Dietary supplements and fatigue in patients with breast cancer: a systematic review - Vieira Teixeira Pereira, Paula Tamara; Reis, Andrea Dias [UNESP]; Diniz, Renata Rodrigues; Lima, Francileia Andrade; Leite, Richard Diego; Pinto da Silva, Mayara Cristina; Meireles Guerra, Rosane Nassar; Moraes Vieira, Erica Brandao de; Santos Garcia, Joao Batista (Springer, 2018)
PurposeCancer-related fatigue (CRF) is defined as a distressing, persistent, and subjective sense of physical or emotional and/or cognitive exhaustion. The treatment of CRF includes pharmacological and non-pharmacological therapies; dietary strategies with promising results have also been used. This study aimed to identify dietary supplements that improve fatigue in patients with breast cancer.MethodsA systematic review of the literature was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Data were obtained from PubMed, Scopus, MEDLINE, CENTRAL, and CINAHL databases using the following MeSH terms: breast neoplasms, dietary supplements, diet, and fatigue. In addition, the Google and Google Scholar search engines were used to find grey literature. Methodological quality was evaluated using the risk of bias in randomised clinical trials in the systematic Cochrane reviews, and the quality of the evidence was also analysed using the GRADE system.ResultsA total of 893 studies were assessed, of which eight were included in the review, with 932 women diagnosed with breast cancer. The most commonly used supplements that improve fatigue were guarana, acetyl-l-carnitine, and co-enzyme Q10. Two studies had a low risk of bias in all categories and three had high-quality evidence.ConclusionsDietary supplements or diet patterns are seldom used to treat fatigue in patients with breast cancer. The results of this review showed that guarana extract and a diet rich in whole foods, omega-3 fatty acids, fruits, and vegetables could be used to treat CRF in patients with breast cancer. The studies had a low risk of bias with high-quality evidence on the efficacy of the interventions in treating fatigue in the study population.
Keywords: Breast neoplasms; Dietary supplement; Diet; Fatigue; Adverse effects